Readings at the Intersection: Social Ecologies in Critical Texts - Holdsworth, Claire (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2017)
Taking extracts from Readings, a short-lived reviews magazine edited by artists Annabel Nicolson and Paul Burwell in 1977, this article explores the intersection between two collectively organized artist-led groups—the London Musicians’ Collective and the London Film-makers’ Co-operative, which were based at the same address between 1977 and 1988. It considers how texts, as extensions of artistic practices, garnered innovative performance criticism and cultures in London at that time. Magazines such as this are posited as a productive means of mapping complex social ecologies and histories involving multiple disciplines.